A rice small GTPase, Rab6a, is involved in the regulation of grain yield and iron nutrition in response to CO2 enrichment. (11th June 2020) - Yang, An; Li, Qian; Chen, Lei; Zhang, Wen-Hao
Abstract: Despite extensive studies on the effects of elevated atmospheric CO2 concentrations ([CO2 ]) on rice, the molecular mechanisms and signaling events underlying the adaptation of plants remain largely elusive. Here, we report that OsRab6a, which encodes a small GTPase, is involved in the regulation of rice growth, grain yield, and accumulation of iron (Fe) in response to elevated [CO2 ] (e[CO2 ]). We generated transgenic plants with OsRab6a -overexpression (-OE) together with OsRab6a- RNAi lines, and found no differences in growth and grain yield among them and wild-type (WT) plants under ambient [CO2 ] conditions. Under e[CO2 ] conditions, growth and grain yield of the WT and OsRab6a -OE plants were enhanced, with a greater effect being observed in the latter. In contrast, there were no effects of e[CO2 ] on growth and grain yield of the OsRab6a -RNAi plants. Photosynthetic rates in both the WT and OsRab6a -OE plants were stimulated by e[CO2 ], with the magnitude of the increase being higher in OsRab6a -OE plants. Fe concentrations in vegetative tissues and the grain of the WT and transgenic plants were reduced by e[CO2 ], and the magnitude of the decrease was lower in the OE plants than in the WT and RNAi plants. Genes associated with Fe acquisition in the OsRab6a -OE lines exhibited higher levels of expression than those in the WT and the RNAi lines under e[CO2 ]. Analysis of our data using Dunnett's multiple comparison test suggested that OsRab6a is an important molecular regulator that underlies the adaptation of rice to e[CO2 ] by controlling photosynthesis and Fe accumulation. Abstract : The small GTPase OsRab6a enhances growth and grain yield in rice in response to elevated CO2 and helps to maintain Fe concentrations in the grain via increasing the expression of genes related to Fe acquisition.